Uso de la soya en acuacultura - Treviño Carrillo, Laura M.
to 50% crude protein (Akiyama, 1992). For this reason, high protein ingredients such as fish meal, bone and blood meal and oil seed meáb varies from 50 to 70% of the feed formulation. The limited supply and high prices of fish meal had encouraged aquaculture nutritionists to consider other alternative protein sources. Nevertheless, high vegetable protein levels in fish diets generally results in low growth rates and poor feed efficiency ratios due to an incorrect essential nutrients balance, raw material antinutritive factors, low palatability or low water stabilis pellets (Lil and Dominy, 1991). Among vegetable meals, the soybean meal is increasing it's use. This is due to soybean chemical composition, amino acid profile and high availabiiity around theworld at lower prices than fishmeal (Akiyama, 1992). Raw soybeans have several antinutritive factors that provokes low growth in cold water fishes. Warm water fishes and shrimps fed with soybean products as the main protein source achieve satisfactory growth. Solvent extracted, dehulled soybean meal is 49% crude protein, from wich, 85% is digestible (for catfish, rainbow trout and tilapia), almost the same as fishmeal (Lovell and Smitherman, 1993) and 89.9%, for shrimp (Akiyama et al 1991). Palatability is the main limiting factor for soybean use in salmon and trout feeds (Lovell and Smitherman, 1993). Whole soybean suitable heated can replace partially (and sometimes totally) fishmeal in freshwater and marine fish. The main recommendation relatd to whole soybean use in fish diets is not to exceed fat levels for each species. One of the main components of soybean oil is soybean lecithin as a mayor source of coline, inositol...